PREVALENCE OF PATELLOFEMORAL PAIN SYNDROME AND ITS ASSOCIATION WITH PROLONGED SITTING, GENDER AND BMI AMONG UNIVERSITY STUDENTS (Journal of Medical & Health Sciences Review, 2025)
Background:University students are at greater risk of musculoskeletal disorders because of lifestyle factors such as sitting for a long time, being inactive, and unsatisfactory posture. Of all these disorders, Patellofemoral Pain Syndrome (PFPS) is found to be quite prevalent, presenting mostly as pain in the anterior knee and interfering with day-to-day functioning. Sitting for a long time, especially while working or studying, gender differences, and differences in Body Mass Index (BMI) are thought to play a major role in the development of PFPS. Though studies abroad emphasize the increasing weight of PFPS in young adults, there is sparse data on its prevalence and correlating risk factors among students at Pakistani universities, particularly in the age range of 18 to 35 years. This seems particularly true in cities where most of the academic classes take place with students often spending prolonged periods of sitting study time with very little exercise.Objectives: To find the prevalence of Patellofemoral Pain Syndrome (PFPS) and its association with prolonged sitting, BMI and gender in students in Universities of Islamabad.Methodology:The study was a descriptive cross-sectional study conducted from February 2024 to July 2024 among 384 students from different universities of Islamabad. The sampling technique used for this study is non-probability purposive sampling (which limited the generalizability of the results). Inclusion criteria included Male and Female students of universities in Islamabad, aged 18-35. A Semi-Structured questionnaire which include demographics data and SNAPPS, which fulfilled the eligibility criteria were used to identify the people with patellofemoral knee pain. Data analysis was performed using SPSS version 29, results were expressed in form of percentages and frequencies. Application of Shiparo-Wilk test showed that the data is right skewed, so Chi-square test and Cramer’s V test were used to find the association.  Results:After the approval from the ethical committee the data was collected. Every participant filled the questionnaire. 90.1% (n=346) individuals out of 384 showed no symptoms of PFPS, 9.9% (n=38) were positive of PFPS. Out of the 38 individuals, females accounted for 81.6% (n=31) in comparison with 18.4% (n=7) of males. Individuals who were PFPS positive, 5.3% (n=2) were obese I 31.6% (n=12) were overweight, 47.4% (n=18) were normal and only 15.8 % (n=6) were underweight, 47.4% (n=18) were in the normal weight category, and 31.6% (n=12) were categorized as overweight while 5.3% (n=2) were classified into the Obese I category, and none in the Obese II category. Additionally, 55.3% (n=21) PFPS individuals reported spending more than 6 hours sitting, 31.6% (n=12) reported spending 4-6 hours per day sitting down and only PFPS individuals 13.2% (n=5) reported spending 1-3 hours sitting daily.Conclusion:The prevalence of PFPS in university students was relatively low. Our current study found a significant association between BMI and PFPS, particularly in the overweight category. This study found no significant association between Sitting hours and PFPS in comparison to previous literature which might be a consequence of choosing a population younger in age than the population included in previous literature. Though PFPS was more prevalent in females, no significant association was observed between gender and PFPS, potentially due to disproportionate number of female participants as compared to males.